Xanthogranulomatous Cholecystitis Mimicking Carcinoma Gallbladder - Elisha Poddar; Prakash Mainali; Suraj Shrestha; Pratima Gautam; Anuradha Twayana; Niharika Pathak; Ashish Tiwari; Abhishek Bhattarai; Laligen Awale; Prasan Singh Kansakar (Case Reports in Hepatology, 2023)
Xanthogranulomatous cholecystitis (XGC) is a rare benign chronic inflammatory disease of the gallbladder that often presents as cholecystitis and can mimic gallbladder carcinoma. Distinguishing XGC from gallbladder cancer preoperatively is challenging. We present a case of a 62-year-old male who presented with features of carcinoma gallbladder in the CECT abdomen and MRCP. Intraoperatively, there was a mass in the gallbladder and extension into the adjacent structures with involvement of the hepatic artery, 1st part of the duodenum, portal vein, and hepatic flexure of the colon, and thus a palliative cholecystectomy was done. The histopathological report came out as XCG. The case aims to outline the clinical presentation of XGC and differentiate it from carcinoma gallbladder.